(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the views of the prominent 16th-century historian and philosopher Khondamir on the concepts of morality and justice from a philosophical perspective. The author analyzes the moral and spiritual foundations of human perfection, emphasizes the necessity of establishing justice as a basis for social order, and reveals the philosophical essence of the interrelation and harmony between morality and justice in human society.